Persepsi Mahasiswa Universitas Bung Karno Terkait Ketahanan Ideologi Nasional Menghadapi Ancaman Ideologi Kapitalisme Global - Salomon A.M. Babys; Edik Prayitno (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
Abstract The phenomenon of globalization which propagates the values of capitalism when compared with the values and philosophy of life of the Indonesian people which are grounded in Indonesian socialism (Pancasila) is a contradictory value, therefore it can be said that globalization has a propaganda purpose which is a serious threat to the existence of the ideological values of Pancasila. The author feels it is important in studying the "perceptions of Bung Karno University students regarding the resilience of national ideology in the era of global capitalism. This research is based on three objectives namely; First; find a detailed understanding of the resilience of national ideology, second; knowing the understanding of UBK students regarding the threat of national ideology, third; find student perceptions related to solutions to maintain national ideology. This research is a development research using descriptive qualitative method. The data analysis method of this study uses the audience reception analysis method, using a critical paradigm. The research results conclude that; First, Bung Karno University students understand the meaning of capitalism substantially, but have not been able to explain the form of its manifestation in today's real life. Second; students in explaining capitalism in sync with Bung Karno's view that capitalism is in the form of subjugation of the order and regulation of the national economic order, cultural colonization, destruction of national sense of nationality, subversion of science, technology, political system, law, and Pancasila ideology. third; students state that the contradictions of capitalism and Pancasila are not easy to identify because of collisions with complex real life realities and the non-implementation of Pancasila ideology itself, fourth; that besides being optimistic students do not see any ideological threats in campus life but they are aware of threats from individualism, liberalism and capitalism, sectarian ideology including the development of a society that has no ideology. Students see a new threat to Pancasila ideology from games as part of the wa proxy. therefore Proxy war is seen as a latent danger of the current Pancasila ideology. Fifth; Students are of the view that to resolve the degradation of Pancasila values, it is important to have education and a system protector for filtering foreign cultural values that conflict with national cultural values. Key word: Perception, resilience, national, ideology, capitalism